Hands-On Artificial Intelligence with Java for Beginners: Build Intelligent Apps Using Machine Learning and Deep Learning with Deeplearning4j - Joshi, Nisheeth (Packt Publishing, Limited, 2018)
This book will introduce the AI algorithms to the beginners and will take on implementing AI tasks using various Java-based libraries. It will take a practical approach to get you up and running with building smarter applications using Java programming knowledge.